Renewal of the Criminal Justice System Through the Constante Justitie Principle That Guarantees Justitiabelen's Satisfaction - Fence M. Wantu; Jufryanto Puluhulawa; Anis H. Bajrektarevic; Mellisa Towadi; Vifi Swarianata (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
The Principle of Constante Justitie, or the principle of a simple, fast, and light trial, is intended so that handling cases can be resolved in a short time. It does not need to take a long time. The problem in this paper is: (1). how is the application of the Constante Justitie principle or the simple, fast, and low-cost principle as expected by justitiabellen? (2). How to renew the criminal justice system through the principle of Constante Justitie, which can guarantee justitiabellen satisfaction. This research is normative juridical research, namely legal research that aims to find methods, norms, or das sollen. The results showed that the application of the principles of justice, speed, and light costs that guarantee justitiabellen satisfaction has not been following the mandate of laws and regulations. The renewal of the criminal justice system, especially the Principle of Constante Justitie, which can guarantee justitiabellen satisfaction, has now been pursued by the Supreme Court by issuing various regulations such as the Supreme Court Rules or PERMA or Supreme Court Circulars or SEMA, but it has not been successful.